Los conflictos internacionales con Irán y Corea del Norte (I): el proceso negociador - Marquina, Antonio (UNISCI Discussion Papers, 2007)
The article details the negotiation process to solve the conflict created by the nuclear pretensions of Iran and the Democratic People’s Republic of Korea, as well as the regional political and segurity context. The article is divided into two parts. The first one, published in this issue, details as far as possible the negotiation process, the presented proposals and the different positions. For a clearer understanding, the dilemmas and red lines set by the U.S. Administration —which go further than what is established in the Non-Proliferation Treaty— are explained; and also the reasons for this position: Iran’s clandestine nuclear program, and the DPRK’s “admission” of the existence of a clandestine nuclear enrichment program. The assumptions, problems, lack of security guarantees and deep mistrust in these two states with regard to the U.S. policies and intentions are analyzed. A second part will explain in more detail the regional political and security implications.